Design of Control System Trainer Based on IoT as Electronic Learning Media for Natural Science Course - Mochammad Sukardjo; Vina Oktaviani; Siska Tawari; Iqbal Alfajar; Ilmi Zajuli Ichsan (Jurnal Penelitian Pendidikan IPA, 2023)
The development of controller system trainer based on Internet of Things (IoT) is one of the online learning media for practical activities that can motivate students in the natural science learning process so the student’s competence in learning can be achieved. One indicator of quality education is that their alumnus has a good knowledge, skills and attitudes. This study aims to develop an IoT-based trainer controller systems as a learning media in electronic 2 of natural science course. The trainer control system in this study used a website developed in accordance with the electronic 2 course which is connected to the trainers in the Electronic’s Laboratory via arduino uno microcontroller on trainer. This control system trainer is a development of basic physical law theory that emphasizes Kirchoff's laws using Maxwell's equations. Where the discussion in the electronics course 2 emphasizes the working principle of transistors. The research method used is the Research and Development (R&D) method with the product development model used is the Borg and Gall model. Product testing describes the design of assessment, type of data, data collection instruments and data analysis techniques. The instrument used in this study is a questionnaire for the material expert test and the media expert test. The data analysis technique used the content validity ratio (CVR) method. Based on the test result of material experts and media experts, the result of high validity was obtained. The result of blackbox testing get 100% results. Based on the test results, it can be concluded that the tool can work well which can remotely from a far using Arduino Mega and ESP8255 with the delay about 2 seconds. The test results for students' psychomotor skills get an average of 63.20 which means Good. So that this trainer control system can be used as a student independent learning media in natural science course